PSYCHO-EMOTIONAL CLIMATE TO REDUCE THE RISK OF DROP OUT IN THE CONTEXT OF HIGHER EDUCATION - Gintere, Ērika (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
The high number of students who have dropped out of higher education prompts to find out both the reasons for dropping out and the causes of dissatisfaction. The psycho-emotional climate of an educational institution is considered to be one of the indicators of the quality of the institution's organizational culture and performance, which determines its pedagogical effectiveness. Therefore, at the moment when the idea of institutional accreditation seriously marks its place in the accreditation process, there is a growing interest in research, the subject of which is the psycho-emotional climate of a higher education institution as a pedagogical resource. The aim of this publication is to identify the psycho-emotional risks of drop out among the students. The research methodology consists of a set of qualitative data obtained by surveying 50 students who have expressed an intention to drop out. The study data were analysed using the qualitative data processing program NVivo 12.0. The study analysed and described the theoretical framework of the psycho-emotional climate and identified the main risks of drop out. It is concluded that the psycho-emotional climate is an essential component of students' desire to continue their studies, as it promotes the institutional sense of belonging and learning achievements. The results of this study complement existing research with qualitative data, operationalizing psycho-emotional support in higher education settings.